Validity and Reliability of the Turkish Version of the Thirst Distress Scale in Patients on Hemodialysis - Belgüzar Kara, PhD, RN (Elsevier, 2013)
Purpose: Thirst has been reported as an important source of distress for patients on hemodialysis. However, there is no instrument available that assesses thirst distress of Turkish patients on hemodialysis. Therefore, the aim of this study was to examine the psychometric properties of the Turkish version of the Thirst Distress Scale (TDS-T) for patients on hemodialysis. Methods: This study was conducted methodologically. A convenience sample of 142 Turkish patients on hemodialysis participated in this study. Data were collected by using a questionnaire, the TDS-T and a visual analogue scale for thirst intensity. The analysis of data included descriptive statistics, the one-sample Kolmogorov-Smirnov test, Kruskal-Wallis test, Mann-Whitney U test, correlation coefficients and psychometric tests. Results: The TDS-T demonstrated acceptable internal consistency (Cronbach's alpha coefficient = .81), good test-retest reliability (intraclass correlation coefficient = .88), and correlations with interdialytic weight gain values and thirst intensity scores (measured by visual analogue scale) indicating concurrent and convergent validity, respectively. Construct validity was supported by known-group comparisons. The results revealed a one-component structure of the instrument. Conclusions: The psychometric properties of the TDS-T were consistent with those reported in the original study. The TDS-T was found to be a valid and reliable tool for evaluating thirst distress in patients on hemodialysis.